Spectrophotometric Determination of Total Flavonoid Content in Biancaea Sappan (Caesalpinia sappan L.) Leaves - Nurlinda Nurlinda; Virsa Handayani; Faradiba Abdul Rasyid (Faculty of Pharmacy, Universitas Muslim Indonesia, 2021)
AbstractBiancaea sappan (BS) is traditionally used to treat anticonvulsants, anti-inflammatory, antiproliferative, anticoagulant, antiviral, immunostimulant, antioxidant, and antimicrobial treatments. Flavonoids are found in Secang; flavonoids are secondary metabolites that have antioxidant activity. This study aims to identify the flavonoids using TLC and determination of flavonoids content in BS leaves. Initially, The methanol extract of BS was obtained by maceration with ethanol. The qualitative analysis of flavonoid was using TLC and visualization by sprayed with AlCl3. The determination of total flavonoid content is conducted based on the AlCl3 method with total flavonoids expressed in QE (Quercetin equivalent) at the maximum wavelength of 431 nm. The research results showed that BS leaves contain flavonoids and the total flavonoid content of BS leaf extract is 1.0318 mg QE / g extract.Keywords: Caesalpinia sappan; Flavonoid content, Spectrophotometric